2014
DOI: 10.20344/amp.4785
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Abscess Secondary to Xanthogranulomatous Cholecystitis

Abstract: Acta Med Port 2014 Jul-Aug;27(4):511-514 RESUMOUma das complicações conhecidas da litíase vesicular consiste na perfuração da vesícula com consequente formação de abcessos colecisto-cutâneos ou trajectos fistulosos externos. Actualmente este tipo de complicação é pouco frequente na prática diária, tendo sido mais frequente. Os autores relatam o caso de uma senhora de 86 anos, acamada e dependente, referenciada à nossa instituição por apresentar uma tumefacção no quadrante superior direito, com sinais inflamató… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Our results showed that the perforation and abscess formation was more common in XGC patients than in GBC patients, which is consistent with other case reports. 8,11,12 In addition to clinical manifestations, serological tests also showed significant differences between XGB patients and GBC patients. As for the serum levels of the most commonly used gastrointestinal tumor markers such as CA19-9, CA 125, AFP, CA 242, and CEA, our study presented a quite interesting result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that the perforation and abscess formation was more common in XGC patients than in GBC patients, which is consistent with other case reports. 8,11,12 In addition to clinical manifestations, serological tests also showed significant differences between XGB patients and GBC patients. As for the serum levels of the most commonly used gastrointestinal tumor markers such as CA19-9, CA 125, AFP, CA 242, and CEA, our study presented a quite interesting result.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of biliary fistula/gallbladder perforation was significantly higher (p = 0.045) in XGC patients than in GBC patients, which is consistent with other reports. 3,[8][9][10] Also, GBC patients presented a significantly higher percentage of chronic infection exposure (p < 0.001). Few statistical differences were encountered in jaundice, perforation and abscess formation, hyperlipidemia, and diabetes between these XGC patients and GBC patients.…”
Section: Clinical Characteristicsmentioning
confidence: 95%